Preparation of Ionic Liquid-Silica Nanoparticles Nanocomposite Film Coated Porous Copper Wire for SolidPhase Microextraction of Pesticides from Tomato Samples - Parviz Aberoomand Azar; Javad Noroz Haghi; Seyed Waqif Husain; Mohammad Saber Tehrani (Journal of Optoelectronical Nanostructures, 2023)
In this study, a new solid phase micro extraction (SPME)fiber coated by sol-gel technology based on polyethyleneglycol (PEG) grafted ionic liquids (ILs), and silicananoparticles (silica NPs) on a porous copper substratewas fabricated. The as-prepared fiber (PEG-ILs-silicaNPs) was then used to extract a variety of pesticides intomato samples before prior to their gas chromatographyflame ionization detection (GC-FID). The key parametersinfluencing extraction efficiency containing includingextraction time, stirring rate, extraction temperature, pH,ionic strength, and desorption temperature, and time wereinvestigated and optimized. The relative standarddeviations (RSDs) for single fiber repeatability rangedfrom 1.2 to 4.6% (n=6), and the RSDs for fiber-to-fiberreproducibility (n=6) were 3.3–6.8%, respectively. Theproposed method based on the PEG-ILs-silica NPs fiberwas successfully applied for the determination of targetedpesticides in tomato samples with good recoveries from89.8 to 103.5% (RSDs=2.1-6.9).